Studies and sport at the University - problems and benefits of sport at University Club Studia i sport akademicki - trudności i korzyści wypływające z uprawiania sportu w ramach KU AZS - Kajetan Suchecki (Kazimierz Wielki University, 2016)
Summary                 University Sports Association is one of the most active student organizations in Poland. Most members of the AZS are students who, between the duties of studying, do sports and represent their universities on academic competitions. Sport during the studies required to mobilize the time between the obligations related to learning which is not always easy.                 This paper is based on the analysis of an available literature and a research conducted through a questionnaire survey among active members of the  AZS University Club at the University of Economics in Katowice. The aim of this article is to answer the question as sports in the Club and activities in AZS effect on school results and developing skills of students.                 In the conclusions we presented different effects of sport on academic results, referring both to the amount of time devoted to learning, as well as its quality.   Keywords: AZS, University Sports Association, students, learning, university       Streszczenie                 Akademicki Związek Sportowy jest jedną z najprężniej działających organizacji studenckich w Polsce. Większość członków AZS to studenci, którzy, między obowiązkami uczelnianymi, uprawiają sport i reprezentują swoje uczelnie na zawodach akademickich. Uprawianie sportu w trakcie studiów wymaga wygospodarowania czasu między obowiązkami związanymi z nauką, co nie zawsze jest łatwe.                 Niniejsza praca jest stworzona na podstawie analizy dostępnej literatury oraz badania przeprowadzonego za pomocą kwestionariusza ankietowego wśród aktywnych członków Klubu Uczelnianego AZS Uniwersytetu Ekonomicznego w Katowicach. Celem artykułu jest odpowiedź na pytanie, jak uprawianie sportu akademickiego w ramach Klubu Uczelnianego i działalność w AZS wpływa na wyniki w nauce i rozwijanie umiejętności studentów. We wnioskach przedstawiono różny wpływ sportu na wyniki w nauce, odnosząc się zarówno do ilości czasu poświęconej nauce, jak i jej jakości.   Słowa kluczowe: AZS, Akademicki Związek Sportowy, studenci, uczenie się, szkoła wyższa